HUBUNGAN BERAT BADAN BAYI LAHIR, ASI EKSKLUSIF, POLA ASUH PEMBERIAN MAKAN DENGAN KEJADIAN STUNTING PADA BALITA DI PUSKESMAS TANJUNG LENGKAYAP - Amalia Lestari; Chairunnah Chairunnah; Rizki Amalia; Arie Anggraini (LPPM ISTeK ICsada Bojonegoro, 2023)
Toddlers are children under five years of age. Toddlerhood is an important period in the process of human growth and development because growth and development takes place quickly. According to WHO (World Health Organization) in Global Nutrition Targets 2025, stunting is considered an irreversible growth disorder which is largely influenced by inadequate nutritional intake and repeated infections during the first 1000 days of life. World Health Organization the incidence of stunting in the world reaches 22% or as many as 149.2 million in 2020. The purpose of this study was to determine the relationship between birth weight, exclusive breastfeeding, parenting style of feeding with the incidence of stunting in toddlers at the Tanjung Lengkayap Health Center. This type of research uses a research design cross sectional. The population in this study were all toddlers who visited the Totorejo Health Center. The sample in this study used a total sampling of 50 toddlers. Data were analyzed by test Chi-Square. Univariate analysis showed that there were 3 toddlers with stunting (6%), while toddlers who were not stunted were 47 respondents (94%). The results of bivariate analysis found that there was a significant relationship between birth weight where the value (P-Value = 0.014), there is a significant relationship between exclusive breastfeeding where the value (P-Value = 0.023), there is a significant relationship between feeding parenting where (P-Value = 0.007) with the incidence of stunting in toddlers at the Tanjung Lengkayap Health Center. In conclusion, there is a relationship between birth weight, exclusive breastfeeding, and parenting style of feeding with the incidence of stunting in toddlers. It is expected that mothers pay attention to child nutrition as well as during pregnancy to maintain a balanced nutritional pattern, provide exclusive breastfeeding and maintain proper feeding parenting patterns for children.